Analysis of risk factors associated to cytomegalovirus infection in dentistry students - Claudia De la Tejera-Hernández; Daniel Noyola; Luis Sánchez-Vargas; Nadya Nava-Zárate; Esperanza De La Cruz-Mendoza; Araceli Gómez-Hernández; Saray Aranda-Romo (Universidad de Concepción., 2015)
Objective: The purpose of the study was to analyze the association between cytomegalovirus (CMV) infection in dental students with occupational risk factors and a genetic trait (NKG2C gene deletion). Study design: Case-control study. 176 students were included and divided in two groups according to CMV serological results: those with CMV infection (case group) and those without prior infection (control group). Demographic, occupational, and the presence of NKG2C gene deletion were compared between both groups. Results: The presence of CMV IgG antibodies was detected in 104 (59.1%) students (case group) while 72 (40.9%) students were CMV negative (control group). The frequency of patient contact, the use of protective barriers, and the number of reported accidents was compared between the study groups; no significant differences were noted. The appropriate use of infection-control measures was observed in the majority of students in both study groups. In the case group the frequency of NKG2C deletion was 9.7% compared to 5.6% in the control group (p=0.33). Conclusion: No association between the presence of CMV infection with occupational and genetic risk factors was found in this population. Dentists should be aware of the CMV prevalence and risks factors associated to this infection, particularly among child-bearing age dentist women.